Investigation Of Changes In The Concentration Of Metals In The Process Of Bacterial Oxidation Of Flotation Concentrate - Kuvandik, Sanakulov; Bakhodir, Mukhiddinov; Sanat, Sharipov (The journal of contemporary issues in business and government, 2021)
The article deals with the behavior of the most important cationic elements, which directly affect the processes of bacterial oxidation of sulfide ores. These are iron, calcium, selenium, arsenic, various modifications of sulfur. In addition to this, data are presented on the appearance of new compounds that promote the dissolution of precious metals, which are selenites, thiosulfates, hydrochloric acid and nitric acid. The main physical and chemical parameters of the studied samples of the bacterial oxidation chain are determined. Possible transformations of the main minerals are established. The tables and figures provide information about changes in the concentration of the main elements during bacterial oxidation. the reasons for changes in the concentration and appearance of new minerals are discussed. The questions of the behavior of organic carbon, the possibility of its activation and the ability to absorb noble metals are covered.